G574(P) Improving patient care through paediatric simulation and multi-disciplinary resuscitation training based upon previous serious incidents at a district general hospital. (27th April 2015) - Halbert, J; Virgilio, M; Dhelaria, A
Abstract : Context: The quality improvement project was undertaken at a District General Hospital and included staff who care for seriously sick or injured children including doctors and nurses working in general paediatrics, accident and emergency and anaesthetics. The appropriate initial assessment and resuscitation of serious ill and injured children together with on-going reassessment and emergency management are essential for reducing morbidity and mortality. Problem: There was no integrated multi-disciplinary team (MDT) paediatric resuscitation training and several paediatric serious incidents had involved more than one department. Simulation training increases the acquisition of skills and provides a platform to review performance and make errors without compromising patient safety. Both the Department of Health and RCPCH recognise the importance of simulation training in improving patient safety through reducing human and system errors. High fidelity manikins can be monitored which significantly adds to their realism. Assessment of problem and analysis of its causes: A retrospective review was undertaken by a paediatric trainee of all the paediatric serious incidents during a ten year period to identify common themes and key recommendations. The development of MDT resuscitation training was one of the principle recommendations to improve the emergency assessment and care provided to children. Intervention: MDT paediatric resuscitation training sessions involving healthcare assistants, nurses, doctors and other allied healthcare professionals from general paediatrics, accident and emergency and anaesthetics were planned several months in advance through a consultation process. Dates and times were chosen to maximise trainee availability and minimise disruption to routine services. For MDT training in accident and emergency, strategies were implemented to ensure patient safety at all times. Resuscitation officers provided support and resuscitation equipment. The hospital switch board was notified so a simulated paediatric crash call could be initiated through the hospital paging system. Scenarios were developed based upon previous paediatric serious incidents to review whether key recommendations had been successfully implemented and sustained. The focus was on familiarisation with paediatric resuscitation equipment, drugs and guidelines in real time as well as teamwork, communication and leadership skills and dynamics between and within the different specialties. A pilot paediatric simulation MDT training session was also undertaken in the Education Centre. Strategy for change: MDT paediatric resuscitation training was coordinated through the paediatric and emergency departments as well as the hospital resuscitation committee. Anonymous feedback through questionnaires was collected from participants. Measurement of improvement: The MDT paediatric resuscitation and simulation training received very positive feedback: "Excellent scenario, felt more real than other simulated scenarios I have attended." Participants found the MDT simulation training much more realistic than weekly departmental resuscitation training with 79% strongly recommending the simulation training compared with just 33% for the weekly departmental training. Effects of changes: MDT paediatric resuscitation training was successfully implemented. A business case was developed for the purchase of a paediatric simulation manikin to improve the reality of the training. Lessons learnt: MDT paediatric resuscitation training is a very valuable tool for improving teamwork and paediatric resuscitation skills. Paediatric high fidelity simulation training can enhance this further through providing a more realistic experience. Message for others: MDT resuscitation training should be routine practice in district general hospitals. Basing scenarios on previous serious incidents is a useful way to review previous key recommendations. A business case can be developed by demonstrating improved experience through a pilot high fidelity simulation trainer.